Comparıson Of Researchers And Technıcs In Three Dıfferent Cephalometrıc Fılm Tracıng Methods - Zafer Sarı; Faruk Ayhan Başçiftçi; Tancan Uysal; Sıddık Malkoç (Galenos Yayinevi, 2002)
Since its first introduction, cephalometric radiographs have gained a wide range of use in scientific research and clinical orthodontics. Different techniques can be used for tracing which have pros and cons. The aim of this study is to compare different tracing techniques and interexaminer differences. Material of the study consisted of 100 lateral cephalograms. These films were traced by either manual tracing, Quick Ceph, Software or JOE software by 2 different researchers. Data were analyzed using ANOVA, Tukey HSD and student t test. Only nasolabial angle showed differences between techniques. Quick Ceph was the fastest method of tracing. Interexaminer differences were related to Frankfort Horizontal and no other significant differences were present.